Australia's National Disability Insurance Scheme: a collaboration opportunity for academia and industry. Issue 3 (2nd July 2018) - Mason, Jonathan; Crowson, Kate; Katsikitis, Mary; Moodie, Michael
Abstract : Purpose: The purpose of this paper is to summarise the initial experiences of Australia's National Disability Insurance Scheme (NDIS). It highlights some of the main challenges being faced by participants, service providers and government, and demonstrates how research can contribute to the ongoing implementation and success of the scheme. Design/methodology/approach: The historical basis for the need for a new approach to disability funding in Australia is explored. The opportunities that exist and the difficulties that are being encountered by those entering and working within the new scheme are discussed. Findings: Several problems were identified including difficult transitions between existing support frameworks to new "NDIS plans", and the risk of market failure. Both the problems and their solutions are discussed and it is hoped that collaboration between the Commonwealth Government, service users, their families, service providers and universities can lead to a number of lasting improvements. Practical implications: The new funding framework provides exciting opportunities for increasing the funding of people with intellectual and physical disabilities in Australia. Developments in technology, service provision in rural and remote areas and the opportunity to meet aspirational life goals exist alongside a number of challenges, including the need to ensure that those with multiple and complex disabilities retain existing levels of support. Originality/value: The implementation of the NDIS is still underway, and opportunities exist to implement changes to the scheme where required. Research findings have an important role to play in the national debate regarding how best to improve quality of life for people with a disability in Australia.